Pengabdian Kepada Masyarakat Melalui Peningkatan Kualitas Sayur Hidroponik dan Pengembangan Smart Farming pada Ismulia Farm - Romano; Nasaruddin; Husna, Rika; Mujiburrahmad (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Based on the results of field observations and the results of the analysis of the existing problem situations in the field, several partner problems were found, namely: 1). Lack of knowledge and skills of partners in increasing production results, by using smart farming technology. 2). Do not understand how to market online and professionally, 3). Do not understand the concept of product packaging, 4). Lack of knowledge about the correct aspects of hydroponic cultivation using the correct planting pattern 5). Do not understand the business management system, and correct bookkeeping administration. The implementation activities will begin with the coordination and socialization stage, then continued with the provision of a smart farming system and training in its use. Continued with Training in Proper Plant Cultivation starting from seeding, planting, and maintenance. Demonstration training on natural pest control using pest traps followed by demonstration training on POC (Liquid Organic Fertilizer) Production and Production of botanical pesticides. The next activity is training in making product packaging. Furthermore, partners will be facilitated with digital marketing and training in its use to facilitate the marketing process, the last activity is to provide counseling on proper business management, administration, and bookkeeping. Based on the results of training and mentoring activities for Ismulia Farm businesses, it can be concluded that partners have increased their knowledge and skills in producing botanical pesticides, liquid organic fertilizers, improving product packaging, natural pest control using pest traps, and increasing their ability to run a business with good planning and understanding business management, and how to develop it (100%). For the smart farming system that monitors remote farming via Android, it is still in the process of finalizing its design.